Faisabilité et disparités des reconversions de l’architecture carcérale française - Alban Prin (Criminocorpus)
The preservation of prison buildings has become a topical issue since the French State has accelerated the process of renewing its real estate stock, threatening the destruction of these buildings, and leading to the mobilization of researchers to ensure that these built testimonies do not disappear. In a tense land context, the compromise found was often that of conversion, posing the question of the difficult balance between respect for the existing and the adequacy of the new uses of the conversion programme. This article is based on a wide-ranging investigation of all the converted prisons in France and, to a lesser extent, of all the prisons demolished since the beginning of the 20th century, and approaches these conversions from the point of view of the feasibility and durability of these architectural operations. Finally, going beyond the preconceived notions, the phenomenon of conversions is rather old – since the 1930s – and counts a not so negligible number of operations, whose stakes and factors of success revolve around the questions of the scale of the building, the adequacy of the programming to the needs of the local authorities concerned, the financials strategies, without neglecting the painful or embarrassing memories of which they are the built testimony.